2013
DOI: 10.1155/2013/286902
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microscopy Assessment of Angiogenesis in Different Breast Cancer Compartments

Abstract: Background/Aim. Tumour angiogenesis defined by microvessel density (MVD) is generally accepted as a prognostic factor in breast cancer. However, due to variability of measurement systems and cutoffs, it is questionable to date whether it contributes to predictive outline. Our study aims to grade vascular heterogeneity by comparing clear-cut compartments: tumour associated stroma (TAS), tumour parenchyma, and tumour invasive front. Material and Methods. Computerized vessel area measurement was performed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Sections with a thickness of 4 µm were cut, mounted on glass slides, and stained with hematoxylin and eosin (H&E) [5]. Using a 20× magnification objective, the specimen images were scanned with a Tissue FAXS automatic scanning system, digitized, and analyzed using HistoQuest software (TissueGnostics, Vienna, Austria) [71].Villus height, crypt depth, and villus height-to-crypt depth ratio of each jejunal tissue section in the small intestines of each mouse were measured to determine if villi and crypts were whole and well-oriented.…”
Section: Histological Analysesmentioning
confidence: 99%
“…Sections with a thickness of 4 µm were cut, mounted on glass slides, and stained with hematoxylin and eosin (H&E) [5]. Using a 20× magnification objective, the specimen images were scanned with a Tissue FAXS automatic scanning system, digitized, and analyzed using HistoQuest software (TissueGnostics, Vienna, Austria) [71].Villus height, crypt depth, and villus height-to-crypt depth ratio of each jejunal tissue section in the small intestines of each mouse were measured to determine if villi and crypts were whole and well-oriented.…”
Section: Histological Analysesmentioning
confidence: 99%
“…Specimens were viewed under the TissueFAXS automatic scanning system, captured by a digital camera and analyzed by HistoQuest software (TissueGnostics, Vienna, Austria). 9 For every jejunal tissue section of each mouse, villus height (VH) and crypt depth (CD) measurements were determined for whole, well-oriented villi and crypts, and these values were averaged.…”
Section: Histology Evaluation Of Jejunal Mucosamentioning
confidence: 99%
“…Angiogenesis, as quantified by microvessel density, is a crucial requisite for tumour growth and is generally accepted as a BC prognostic factor [32,33]. However, microvessel density has been reported to have compartment variability of vessel density within the tumour, highlighting the propensity of an invasive front to link to an active process of angiogenesis [44]. In their recent study, Natrajan et al [45] reported that high microenvironmental diversity was strikingly associated with poor prognosis that could not be explained by tumour size, genomics, or any other data type.…”
Section: Bc and Tumour Microenvironment (Tme)mentioning
confidence: 99%